PKM BUDIDAYA IKAN LELE (Clarias gariepinus) MENGGUNAKAN SISTEM BIOFLOK PADA GURU SMA SE-JAWA TIMUR - Pungky SWK; Vivin Andriani; Diah Karunia Binawati; Sukarjati; Arif Yachya; Dyah Hariani; Susie Amilah (Jurnal Penamas Adi Buana, 2023)
The Cultivation of high-density fish requires artificial feed with high protein content for growth. The higher the protein contained in the feed, the more expensive the feed price, while the feed is the largest cost reaching 60-70% of the production cost. In addition to the problem of feed in high-stocking density fish farming, of course, the waste disposal is also getting higher, which causes failure in the cultivation business. To overcome these problems, it is necessary to make a breakthrough in the cultivation system, one of which is catfish farming using a biofloc system by utilizing heterotrophic bacteria proven to reduce ammonia waste discharge in ponds. The results of this study need to be immediately socialized through training activities for high school teachers. The pretest and post-test results of trainees based on the percentage of activity objectives showed an increase with an average of 55%. It is hoped that the results of the training for high school biology teachers will not only get new knowledge about the application of biofloc to catfish farming. The knowledge gained can be disseminated to students in their schools to support better biology learning